Distribution of Aedes aegypti (Linnaeus, 1762) based on Ovitrap Geodata at Kolongan Satu Village, Central Tomohon, North Sulawesi - Rettob, Thesia; Astuti, Raden Roro Upiek Ngesti Wibawaning; Nugroho, Laurentius Hartanto (Journal of Tropical Life Science, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia, particularly in urban and peri-urban areas where Aedes aegypti thrives. Tomohon City has experienced a significant increase in DHF cases and, in early 2024, ranked among the top five regions with the highest Incidence Rates (IR) in Indonesia. This study aimed to assess the distribution and density of A. aegypti larvae through ovitrap-based surveillance and to evaluate residents' basic knowledge of DHF and its vectors in Kolongan Satu Village, Tomohon City. A cross-sectional study was conducted using larval surveillance and a structured questionnaire. A total of 200 ovitraps were placed both indoors and outdoors in and around 100 houses across five surveillance stations. Egg collection was carried out in two stages. Collected eggs were identified morphologically as A. aegypti. Vector density was analyzed using the Ovitrap Index (OI) and Ovitrap Density Index (ODI). Residents’ knowledge regarding DHF transmission, vector characteristics, and preventive measures was assessed descriptively. The results showed that the OI values during stage 1 were 25.5% indoors and 39% outdoors, while during stage 2, the values were 24% indoors and 35% outdoors, indicating a medium level of vector presence. The ODI increased markedly from 3.21% in stage 1 to 9.72% in stage 2, reflecting a high density of A. aegypti. Most respondents demonstrated good knowledge of DHF, its vectors, and preventive strategies, although some difficulties in understanding scientific terminology were identified and addressed through education. These findings indicate persistent A. aegypti breeding in Kolongan Satu Village and highlight the need for strengthened vector control measures and continuous community-based education to prevent future DHF outbreaks.